Perception of Bank Managers on the Use of Personal Social Media for Bank Product Promotion: A Narrative Study of Nepal - Rajendra Gautam Jaishi (International Journal of Marketing and Digital Creative, 2023)
In the ever-evolving landscape of digital marketing, this qualitative narrative study uncovers the intricate perspectives of three Nepalese bank managers on the use of personal social media platforms to promote their bank's products and services. The most modern qualitative approach that focuses on life stories as the essence of people-oriented sciences is narrative study, therefore the study adopts an interpretivist epistemological perspective and a constructivist realism ontology, employing in-depth interviews to gather rich narratives from the participants. Thematic analysis of the qualitative data revealed four prominent themes: Work-Life Balance, Belongingness, Enforced Instructions, and Boon and Bane. These themes offer theoretical insights into the complex interplay between personal and professional aspects in the context of digital marketing and organizational culture. The study provides valuable insights into how bank managers perceive the use of personal social media accounts for product promotion within Nepal's banking industry.